2015
DOI: 10.1007/s00208-015-1212-1
|View full text |Cite
|
Sign up to set email alerts
|

Stationary isothermic surfaces in Euclidean 3-space

Abstract: Let be a domain in R 3 with ∂ = ∂(R 3 \ ), where ∂ is unbounded and connected, and let u be the solution of the Cauchy problem for the heat equation ∂ t u = u over R 3 , where the initial data is the characteristic function of the set c = R 3 \ . We show that, if there exists a stationary isothermic surface of u with ∩ ∂ = ∅, then both ∂ and must be either parallel planes or co-axial circular cylinders . This theorem completes the classification of stationary isothermic surfaces in the case that ∩ ∂ = ∅ and ∂ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…We also point out that this result can be obtained under quite general regularity assumptions on ∂Ω , as shown in [16]. The case in which ∂Ω is not bounded is not settled: we mention [12,14] for some partial results in this direction and [8] for a characterization in 3-space.…”
Section: Symmetry In Spacementioning
confidence: 80%
See 1 more Smart Citation
“…We also point out that this result can be obtained under quite general regularity assumptions on ∂Ω , as shown in [16]. The case in which ∂Ω is not bounded is not settled: we mention [12,14] for some partial results in this direction and [8] for a characterization in 3-space.…”
Section: Symmetry In Spacementioning
confidence: 80%
“…In a subsequent series of papers, the same authors extended their result in several directions: spherical symmetry also holds for certain evolution nonlinear equations [11,13,15,16]; a hyperplane can be characterized as an invariant equipotential surface in the case of an unbounded solid that satisfies suitable sufficient conditions [12,14]; for a certain Cauchy problem, a helicoid is a possible invariant equipotential surface [9]; spheres, infinite cylinders and planes are characterized as (single) invariant equipotential surfaces in R 3 [8]; similar symmetry results can also be proven in the sphere and the hyperbolic space [13].…”
Section: Klamkin's Conjecture (1964)mentioning
confidence: 98%
“…The stationary isothermic surfaces of solutions of the heat equation have been much studied, and it has been shown that the existence of a stationary isothermic surface forces the problems to have some sort of symmetry (see [MPeS,MPrS,MS2,MS3,MS5,MS6,MS7,S]). A balance law for stationary zeros of temperature introduced by [MS1] plays a key role in the proofs.…”
Section: Introductionmentioning
confidence: 99%